Analyzing the Social Impact of ESG Programs Through the SDGs Framework and SROI Approach: A Case Study of PT Merdeka Copper Gold Tbk, Platinum Rank ASRRAT 2025 - Tyas Indrayanti; Ida Bagus Ketut Bayangkara (Indonesian Journal Publisher, 2026)
This study analyzes the social impact of Environmental, Social, and Governance (ESG) programs at PT Merdeka Copper Gold Tbk, an Indonesian mining company that achieved Platinum Rank in the Asia Sustainability Reporting Rating (ASRRAT) 2025. Using a qualitative case study approach through document analysis of the company's 2024 Sustainability Report, this research applies the Social Return on Investment (SROI) framework alongside the Sustainable Development Goals (SDGs) and GRI Standards as analytical lenses. The findings indicate that Merdeka allocated USD 5,613,149 toward community development and empowerment initiatives in 2024 an 83% increase from the prior year covering eight social pillars aligned with SDG 1, 3, 5, 6, 8, 12, 13, 15, 16, and 17. SROI analysis demonstrates that the social value generated through education, health, economic empowerment, gender equality, and environmental programs substantially exceeds the investment made. This study contributes to ESG accounting literature in the extractive sector and illustrates how the SROI framework can serve as a qualitative-evaluative instrument for social impact measurement in corporate sustainability reporting.